2009
DOI: 10.1080/02699050903196688
|View full text |Cite
|
Sign up to set email alerts
|

The effect of internet-based cognitive rehabilitation in persons with memory impairments after severe traumatic brain injury

Abstract: These results suggest that the Internet may be an effective delivering mechanism for compensatory cognitive rehabilitation, particularly among individuals who are already utilizing some basic compensatory strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 16 publications
3
67
1
2
Order By: Relevance
“…Among those who perceived as having good computer skills, some respondents perceived as having decreased memory (OR 1.9), whereas others felt increase (OR 2.8) instead, when comparing with those rating as having poor/ average skills. In addition, the youngest age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) felt that Internet use improved their memory significantly more often (OR 4.0) compared to the oldest age group. The difference between workers and nonworkers was also statistically significant; workers (OR 0.4) were less likely to feel increase of memory resulting from Internet adoption compared to those not in the working life.…”
Section: Descriptive Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Among those who perceived as having good computer skills, some respondents perceived as having decreased memory (OR 1.9), whereas others felt increase (OR 2.8) instead, when comparing with those rating as having poor/ average skills. In addition, the youngest age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) felt that Internet use improved their memory significantly more often (OR 4.0) compared to the oldest age group. The difference between workers and nonworkers was also statistically significant; workers (OR 0.4) were less likely to feel increase of memory resulting from Internet adoption compared to those not in the working life.…”
Section: Descriptive Analysismentioning
confidence: 96%
“…Much of the existing studies have focused on Internet's and ICT roles in (online) learning 14 as well as new technology's role in online-based cognitive therapy [15][16] and as a support tool for those with existing brain dysfunctions. [17][18][19] Therefore, it is pertinent that such cognitive abilities and their relationships with Internet adoption are assessed from different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…18 A subsequent study showed significant improvements in compensatory strategies (e.g., calendar use, use of a cue card) and significant family-reported improvements in functioning (e.g., improved patient mood, fewer memory problems) after 60 sessions of cognitive rehabilitation via the Internet. 19 Arguably, individuals completing this therapy received sufficient experience with the IM system to make an informed decision about whether they perceived their treatment to be effective and whether they would recommend it to others with similar cognitive impairments. To the best of our knowledge, a study concerning patient satisfaction with this type of cognitive teletherapy has not been previously done.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only one completed study on internet-based cognitive rehabilitation [67], which was conducted in patients with memory impairments after severe traumatic brain injury. In this study, although there were no significant differences observed between the active and control conditions on the primary outcome measures (patient-and family-rated mood and memory), the authors suggest that the internet may still be a useful means of delivering compensatory cognitive rehabilitation [67]. They also report that patients were highly satisfied with the treatment [68].…”
Section: Expert Commentarymentioning
confidence: 99%